(a 11)(a 11) Step-by-step explanation:

(a 11)(a 11) Step-by-step explanation:

The factored form is . Step-by-step explanation: Given : We have to write the given expression in factored form. Factor form of an expression is writing the expression in lower power form such that the product of factors given the original expression Consider the given expression . We know the algebraic identity Here . Comparing with identity stated above , we have x= a , b = 11 , thus, we get . Thus, the factored form is .

121=11.11 a^2-11^2 (a-11). (a 11) a.a 11a-11a-11.11 a^2 0-121 a^2-121

(a 11) (a-11) Step-by-step explanation:

A^2 11^2 = ( a 11 )( a 11 ), because we have the formula difference of squares, a^2 b^2 = ( a b )( a b );

121=11.11 a^2-11^2 (a-11). (a 11) a.a 11a-11a-11.11 a^2 0-121 a^2-121

so the second choice is right sure

121=11.11 a^2-11^2 (a-11). (a 11) a.a 11a-11a-11.11 a^2 0-121 a^2-121

This post is last updated on hrtanswers.com at Date : 1st of September – 2022